Kurikulum Merdeka dalam Konsepsi Pendidikan Syekh Nawawi Al-Bantani - Fradana, Heru (MAN 1 Kota Kediri, 2024)
Education is one of the ways to advance human civilization. Historical records reveal that the better education during a particular period, the better civil society developed. A dynamic development in education is needed to create a better civilization. In the era of globalization, education has a heavier task than ever before, the boundaries of space and time are no longer known in this era. The ease of access to information has both positive and negative impacts. While it is beneficial for knowledge, the incoming facts may not be filtered according to the culture and norms of a particular region or country, resulting in the loss of character and national identity. In this regard, the Ministry of Education provides a solution of the form of a learning curriculum, namely the